Manajemen Diri: Upaya Percepatan Profesionalisme Guru Taman Kanak-Kanak Dan Sekolah Dasar Di Kecamatan Sukodono Sidoarjo - Dewie Tri Wijayati; Jun Surjanti; Hujjatullah Fazlurrahman; Hafid Kholidi Hadi; Achmad Kautsar (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Teacher professionalism through Professional Development. In order to fulfill the establishment of professional mental formation of course begins with the name of self-building, to create self-confidence teachers should be given briefing about self-management, to manage himself through the management function,that is to create, organize, coordinate, and control and build themselves. This PKM method is training of teacher professionalism in self management. The training was attended by 70 teachers from the Al Qusaeni Foundation. PKM results seacra general PKM activities can improve professionalism. In terms of facilities and infrastructure: the procurement of consumption, committee, style of equipment (LCD, Whiteboard, seminar kit, etc.) and building is useful